Comparação da Cobertura Jornalística Entre Portais de Notícias e YouTube: Um Estudo de Caso do Conflito entre Israel e Palestina - Martins, Victor; Almeida, Jussara M.; Gonçalves, Marcos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16193, 2025)
This study systematically investigates how the journalistic coverage of the same event can vary depending on the dissemination platform and the communication vehicle. The research focuses on the coverage of the Israel-Palestine conflict, analyzing content from official news portals and the YouTube channels of major mass-reach media organizations. To this end, we employed Natural Language Processing (NLP) techniques to comparatively characterize both the texts published on the portals and the video transcripts aired on the respective YouTube channels. For sentiment analysis, we utilized the TextBlob and VADER algorithms. Furthermore, we applied text similarity methods, such as the Longest Common Subsequence (LCS) technique and the SBERT (Sentence-BERT) model, to measure the degree of resemblance between headlines and correlated content. This helped to identify when seemingly similar texts actually converge or diverge in their focus. Using BERTopic, it was observed that, despite the existence of similar headlines between portals and videos, the associated texts frequently address distinct themes or emphasize varied aspects of the conflict. This methodological combination allowed us to demonstrate that the journalistic narrative is not uniform and can be significantly influenced by the dissemination platform, even when the base event is the same.